2013
DOI: 10.1111/echo.12472
|View full text |Cite
|
Sign up to set email alerts
|

Defining Characteristics of Early Adopters of Multimodality Cardiovascular Imaging

Abstract: Board-certified specialists in MMI tend to be younger cardiologists than those engaged in single-modality cardiac imaging. There are few advanced (3 modality) MMI practitioners in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…These included younger age of the respondent and fewer years in one's current VA role. This finding is consistent with other studies that have also found that younger and more recently trained clinicians are more likely to be early adopters of innovations [32]. Alternatively, this association could be the result of an unmeasured confounder.…”
Section: Discussionsupporting
confidence: 92%
“…These included younger age of the respondent and fewer years in one's current VA role. This finding is consistent with other studies that have also found that younger and more recently trained clinicians are more likely to be early adopters of innovations [32]. Alternatively, this association could be the result of an unmeasured confounder.…”
Section: Discussionsupporting
confidence: 92%
“…This nding is consistent with other studies that have also found that younger and more recently trained clinicians are more likely to be early adopters of innovations. 32 Alternatively, this association could be the result of an unmeasured confounder. Future work should assess how team member characteristics relate to their use of speci c implementation strategies and their success.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with other studies that have also found that younger and more recently trained clinicians are more likely to be early adopters of innovations. 26 Alternatively, this finding could be the result of an unmeasured confounder. For example, younger respondents could be present in sites with bigger teams with more capacity to delegate tasks.…”
Section: Discussionmentioning
confidence: 99%